Adherence to statins is associated with reduced incidence of idiopathic venous thromboembolism: real-life data from a large healthcare maintenance organisation. Issue 24 (4th October 2012) - Rabinowich, Liane; Steinvil, Arie; Leshem-Rubinow, Eran; Berliner, Shlomo; Zeltser, David; Rogowski, Ori; Shalev, Varda; Raz, Raanan; Chodick, Gabriel
Abstract : Objective: Previous reports on the association between statin use and venous thromboembolism (VTE) did not examine patient adherence to medications, thus their applicability in a real life setting is questionable. Our objective was to investigate the association between the use of statins and incidence of first ever idiopathic VTE. Design: A retrospective cohort study. Settings: A large healthcare maintenance organisation. Patients: Included were statin initiators aged 30 years or older since 2003 who did not have a statin prescription for at least 4 years before that and had at least 18 months follow-up. Excluded were patients with known risk factors for VTE. End of follow-up was defined as the first of the following: leaving Maccabi Healthcare Services, death, VTE or October 27, 2010. Interventions: Prescription drug purchase data was analysed in order to evaluate the association between statin use and adherence and between VTE prevention. Main outcome measures: VTE diagnosis during follow-up. Results: The study population included 127 822 subjects (53 618 females). The follow-up period was comprised of 594 190 patient years, and included 1375 VTE cases and 5-year cumulative incidence rate of 1.15%. Cox regression analysis demonstrated a significantly lower VTE risk of 19% and 22% in the more adherent patient groups, compared to the risk for the lowest adherence group. The simvastatin dose, the most frequently prescribed statin, was negatively associated with the risk of VTE. Conclusions: In a real life healthcare maintenance organisation setting, better adherence to statins is associated with a reduced risk of first ever idiopathic VTE events.